Screening for obstructive sleep apnoea in patients with treatment-resistant depression: a case–control study. Issue 2 (April 2018) - Asaad, Tarek; Barakat, Doaa; Elwasify, Mohamed; Aziz, Karim A.; Elwasify, Mahmoud; El-Gabry, Dina A.
Abstract : Background: Obstructive sleep apnoea (OSA) and major depressive disorder have a reciprocal and overlapping relationship with studies showing a high prevalence of depressive symptoms in OSA and an increased prevalence of sleep disturbances in major depressive disorder, but to date risk of OSA in treatment-resistant depression (TRD) has not been investigated. Therefore, we aimed to investigate the risk of OSA in patients with TRD. Patients and methods: We conducted a cross-sectional, case–control study comparing 100 patients with TRD with 100 healthy controls at risk of OSA using the STOP-Bang questionnaire, for daytime sleepiness using the Epworth Daytime Sleepiness Scale and insomnia using Insomnia Severity Index. We correlated between severity of symptoms for depression, OSA, daytime sleepiness and insomnia. Results: Patients with TRD had significantly higher scores ( P <0.05) on the STOP-Bang, Epworth Daytime Sleepiness Scale, and Insomnia Severity Index compared with healthy controls. Depression severity was significantly correlated with severity of risk of OSA, daytime sleepiness and insomnia severity ( P <0.05). OSA severity risk was significantly correlated with daytime sleepiness and insomnia severity ( P <0.05). High-risk OSA patients had significantly higher middle insomnia scores compared with low-risk patients ( P <0.05). Conclusion: Our study was the first to specifically examine for risk of OSA in TRD. We found a significantly higher risk of OSA, more daytime sleepiness and more insomnia compared with healthy controls and a significant correlation of severity between these parameters and depression severity. What is less clear is whether these findings are specific to TRD or occur in other depression populations.